Possible deNO(x) management under net oxidizing conditions: a molecular beam study of (NO)-N-15+CO+O-2 reaction on Pd(111) surfaces - Nagarajan, Sankaranarayanan; Thirunavukkarasu, Kandasamy; Gopinath, Chinnakonda S. (Journal of Physical Chemistry C, 2011)
Isothermal kinetic measurements of (NO)-N-15 reduction with CO on Pd(111) surfaces were carried out under net-oxidizing conditions with (NO)-N-15 + CO + O-2, using a molecular beam instrument (MBI). Transient state (TS) and steady state (SS) kinetic details of the above reaction were obtained for a wide range of temperature and beam compositions, especially with O-2-rich compositions. Increasing O-2 content, generally, suppresses (NO)-N-15 reduction in the SS; nonetheless, irrespective of O-2 content, N-15(2) was produced in TS, and to a significant extent under SS conditions too. Sustainable N-2 production between 450 and 600 K and with low to moderate amount of oxygen was observed, and the extent of NO decomposition was also quantified. The ratio of N-15(2): (N2O)-N-15 was generally found to be around 8:1 under most of the reaction conditions. Maxima in the SS reaction rates of all products were observed between 500 and 600 K. Compared to other elementary reaction steps, a slow decay observed with N + N -> N-2 step under SS beam oscillation conditions demonstrates its contribution to the rate limiting nature of the overall reaction. Fast beam switching experiments have been performed alternately between O-2-lean and -rich conditions, thus highlighting the effectiveness of (NO)-N-15 reduction in TS, irrespective of the beam composition. Possibly in a future technology initiative, this aspect could be exploited to manage more (NO)-N-15 reduction on Pd-based catalysts.